Psychological skills training as a way to enhance an athlete's performance in high-intensity sports - Birrer, D.; Morgan, G. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The importance of psychological skills training (PST) in the development of athletic performance is widely recognized. This paper is a comprehensive review of PST in elite sports, with a special focus on high-intensity sports (HIS). The reviewed literature showed a lack of convincing evidence and theoretical underpinning concerning traditional psychological skills to enhance performance in HIS. Therefore, a model with three conceptual levels (psychological demands, skills and techniques) is presented. The model facilitates the identification of the psychological demands of a specific sport, which in turn enables distinguishing which psychological skills are required. This allows an expert to choose psychological techniques to improve the athlete's psychological skill. Considerations based on our model and the limited HIS-related literature available revealed self-skills, personal development and life skills, arousal-regulation skills, volitional skills, motivational skills and recovery skills as the most important skills to address in order to enhance performance. Development of harmonious passion, in-practice integration of volitional strategies, use of associative attentional techniques, pain management techniques, use of the mindfulness-acceptance approach and the facilitative interpretation of cognitive and somatic sensations are regarded as suitable to meet the psychological demands of HIS. They are recommended for systematic application by athletes and coaches.